2007
DOI: 10.1507/endocrj.k06-129
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy and Vascular Risk Disorders in Adult Hypopituitarism

Abstract: Abstract. Adult patients with hypopituitarism are treated by the replacement of deficient hormones, although GH has not been substituted until March 2006 in Japan except for clinical trial. This study examines which hormonal status influences the prevalence of vascular risk disorders in hypopituitary adults. A sample of 263 adult patients with hypopituitarism was studied, among whom there were various hormonal status such as no deficiency, treated or untreated deficiency of each pituitary hormone. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Several studies have shown a high prevalence of cardiovascular risk factors (hyperglycaemia, hypertension, dyslipidaemia and changes in body composition) in patients diagnosed with hypopituitarism. In the present study, the prevalence of each cardiovascular risk factor was lower than previously reported, probably related to a lower incidence of obesity …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown a high prevalence of cardiovascular risk factors (hyperglycaemia, hypertension, dyslipidaemia and changes in body composition) in patients diagnosed with hypopituitarism. In the present study, the prevalence of each cardiovascular risk factor was lower than previously reported, probably related to a lower incidence of obesity …”
Section: Discussionmentioning
confidence: 99%
“…The initial clinical expression of hypopituitarism is often mild and nonspecific, which can lead to a delayed diagnosis . Compared to the general population, patients with hypopituitarism have increased morbidity and mortality, especially because of cardiovascular disease …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most patients in this study had multiple pituitary hormone deficiencies and the majority of women with gonadotropin deficiency were receiving oral estrogen replacement. As several reports indicate hormone replacement therapy itself plays some role in the development of metabolic disorders including dyslipidemia [14,15], the possibility cannot be ruled out that hormone replacement therapy contributes to the development of dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…18 In humans, a higher prevalence of obesity was suggested in patients with AVP deficiency or in subjects with reduced AVP activity. 19,20 Recently, Enhorning et al 21 studied polymorphism rs1042615 of the V1a receptor in middle-aged humans in southern Sweden (nϭ5506; CC, CT, and TTϭ30.4%, 49.2%, 20.4%) and reported that CTϩTT subjects had significantly higher blood glucose concentration and a tendency toward a higher prevalence of obesity than CC subjects. Similarly, in this study, TT men had slightly higher blood glucose concentration, although not significant, and significantly higher BMI (Figure 1), and, moreover, overweight men in Figure 3 show significantly higher T allele frequency.…”
Section: Bmi and Blood Pressure Before Training And V1a Receptor Polymentioning
confidence: 99%